2022
DOI: 10.37134/jrpptte.vol12.1.4.2022
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and struggles of public senior high school science teachers during the new normal

Abstract: The rapid increase of COVID-19 has brought challenges in the delivery of basic education and forced teachers to adapt the distance learning modality. It is interesting to find out the teachers' experiences in terms of their preparation, teaching engagement, and challenges in the new normal. The study aimed to capture the lived experiences of Senior High School (SHS) science teachers in the new normal education. Specifically, it sought to (a) determine the conception of science teachers on education in the new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…Bartkowiak et al (2022) confirmed the limitations of their study in the aspects of small research sample, the qualitative method itself did not allow for the solid generalization, in addition to its limited scope with the Polish academicians' private and public dimensions. On the other hand, Geverola et al (2022) pointed out that mixed methods of research might address the contextual limitations about the experiences of science teachers in the new normal in the areas of the practices in their preparation, teachinglearning processes, and the activities in the distance learning modality. Fute et al ( 2022) have a high level of research on the predictors of teachers' job satisfaction and the level to which they have influenced teaching satisfaction during the period of COVID-19 pandemic with 2886 Chinese teachers to examine the effects of teachers' work values on their job satisfaction through the mediating role of work engagement.…”
Section: Continuedmentioning
confidence: 99%
See 3 more Smart Citations
“…Bartkowiak et al (2022) confirmed the limitations of their study in the aspects of small research sample, the qualitative method itself did not allow for the solid generalization, in addition to its limited scope with the Polish academicians' private and public dimensions. On the other hand, Geverola et al (2022) pointed out that mixed methods of research might address the contextual limitations about the experiences of science teachers in the new normal in the areas of the practices in their preparation, teachinglearning processes, and the activities in the distance learning modality. Fute et al ( 2022) have a high level of research on the predictors of teachers' job satisfaction and the level to which they have influenced teaching satisfaction during the period of COVID-19 pandemic with 2886 Chinese teachers to examine the effects of teachers' work values on their job satisfaction through the mediating role of work engagement.…”
Section: Continuedmentioning
confidence: 99%
“…The effects of stress, pro-social values or commitment to the teaching profession, and digital competencies explained the varying impacts on teachers' individual work performance (Barkotwiak et al, 2022). Geverola et al (2022) revealed that some of the teachers suffered their wellness from struggles in keeping engaged classes. However, the commitment to teachers' vocations made them adaptable and strove to become better in conducting online education (Geverola et al, 2022).…”
Section: H2: Acceptance Of Work From Home Positively Affects Individu...mentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome the existing needs of the curriculum, teacher training is of utmost importance. In order to achieve universal literacy, teachers need to update their knowledge, skills, and experience to embrace the fourth sustainable developmental goal, i.e., quality education (Geverola, 2022).…”
Section: Introductionmentioning
confidence: 99%